Self-reported social support at works among nurses and associated factors. Results from a cross-sectional study in a provincial hospital in 2020. - Tran Thi Thu, Thuy; Nguyen Thi, Huong; Nguyen Van, Bang; Le Thi Thanh, Xuan (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objective: This study aimed to measure nurses' self-perceived social support and identify associated factors at one Vietnamese provincial hospital in 2020.Methods: A cross-sectional study was implemented among clinical nurses of 22 treatment wards working at the hospital for over six months. Two hundred sixty-one nurses returned the self-reported questionnaires containing the Vietnamese 22-item Job Content Questionnaire and set of questions on personal and work characteristics. Descriptive analysis (frequency, mean, standard deviation), crude analysis (t-test and ANOVA), and multivariate linear regressions were conducted to describe the social support (i.e., supervisor' and co-worker's supports) and their associations with other factors at the significant level p less than 0.05.Results: The study achieved a relatively high response rate (82.1%). Social supports, including supervisor and co-worker's supports, were 24.04, 11.89, and 12.16, respectively. Multivariate Linear regressions showed an inverse association of job demand and positive correlation of job control with both supervisor and co-workers' support among participating nurses (p
Keywords: Social support; supervisor's support; co-worker's support; clinical nurses; provincial hospital; Vietnam